Kardar-Parisi-Zhang universality in two-component driven diffusive models: Symmetry and renormalization group perspectives - Dolai, Pritha; Simha, Aditi; Basu, Abhik (Physical Review E, 2024)
We elucidate the universal spatiotemporal scaling properties of the time-dependent correlation functions in a class of two-component one-dimensional (1D) driven diffusive system that consists of two coupled asymmetric exclusion processes. By using a perturbative renormalization group framework, we show that the relevant scaling exponents have values same as those for the 1D Kardar-Parisi-Zhang (KPZ) equation. We connect these universal scaling exponents with the symmetries of the model equations. We thus establish that these models belong to the 1D KPZ universality class.
CRIS-Team Scopus Importer:2024-06-28